Postgraduation Activities All Degree Levels in Pennsylvania, 1977 / William F. Donny. - Donny, William F. (Distributed by ERIC Clearinghouse, 1978)
Details of relationships between employment demand and the supply of graduates of various degree fields and degree levels from all types of institutions in Pennsylvania in 1977 are presented. Data on 45,078, or 50.5 percent of the higher education graduates at all degree levels, represents graduates' status five to six months after their graduation. All state and community colleges and two-thirds or more of state-aided and private junior colleges were not included. Postgraduate activities for graduates from 23 major disciplines are reported for the following five degree levels: bachelors, masters, doctoral, first-professional, and associate. Approximately 50 statistical tables are included, and some of the findings are summarized in the text. It was found that bachelor degree graduates experienced high employment rates if they had majored in computer sciences, engineering, or the health professions. A weak job market was experienced particularly by bachelor degree graduates in area studies, biological sciences, foreign languages, letters, psychology, social studies, and interdisciplinary studies. At the graduate levels employment was increasingly favorable, and a high percentage of associate degree graduates went on to further education. (SW)